Radio and television spot announcements for family planning worldwide - Bonnie Remsberg;Dan Price;Jane Trowbridge;George Daffin ([Chicago] : Communication Laboratory, Community and Family Study Center, University of Chicago, 1975)
This volume is one of a series dedicated to improving the content of family planning communication-education programs. Its central theme is that many of the most severe and critical problems facing family planning programs can be alleviated by the use of properly worded spot announcements. It seeks to rove this by providing specific examples.
Chapter One. Introduction: spot announcements and the 25 critical obstacles to family planning -- Chapter Two. What makes a spot announcement effective -- Chapter Three. Pretesting spot announcements -- Chapter Four. Radio and television spot announcements and the 25 critical obstacles
Based upon Twenty-five communication obstacles to the success of family planning programs, by D.J. Bogue.
Keywords: TELEVISION IN FAMILY PLANNING